CRESCIMENTO E BIOFIXAÇÃO DE CO2 NO CULTIVO DE CHLORELLA EM FOTOBIORREATOR EM FUNÇÃO DE DOSES DE CARBONO ORGÂNICO - SALLES, Jussara Souza,; BINOTTI, Flávio Ferreira da Silva,; SALLES, Josiane Souza,; FERREIRA, Elen Saturnino,; RANDO, Fabiana dos Santos,; COSTA, Edilson, (ANAIS DO ENIC, 2023)
-